Effect of Mn Element Addition on the Microstructure, Mechanical Properties, and Corrosion Properties of Mg-3Zn-0.2Ca Alloy - Han, Yu Yan; You, Chen; Zhao, Yun; Chen, Min Fang; Wang, Liang (Frontiers in Materials, 2019)
Magnesium-zinc-calcium alloys have unique advantages of being used as biomedical bone implants since their mechanical properties and biocompatibility are similar to human tissues. However, insufficient strength and poor corrosion resistance have been the major problems to stunt the application. In this paper, the changes of microstructure, mechanical properties and corrosion resistance of ternary Mg-3Zn-0.2Ca(wt.%) with different contents of Mn (0.3, 0.5, 0.7, 0.9, wt.%) are studied. With the increase of Mn content, the grain size of as-cast alloy first decreases and then increases, this indicates that the amount of Mn affects the degree of subcooling of the alloy. At the 320℃/24h homogenizing treatment, the large and uneven dendrites are transformed into uniform equiaxed grains, the mechanical properties of alloys with different Mn contents are different on the basis of Mg-3Zn-0.2Ca(wt.%) alloy. The five alloys were extruded into bar with a diameter of 8 mm through hot-extrusion process. Quaternary Mg-3Zn-0.2Ca-XMn (X=0.3, 0.5, 0.7, 0.9) (wt.%) alloys are investegated and the results show that 0.5wt% Mn alloy has the best yield tensile strength (YS) (302MPa) and good ultimate tensile strength (UTS) (327MPa). The reason is that the different contents of Mn restrain the dynamic recrystallization in extrusion process, which remarkedly reduced the grain size. Moreover, each alloy is investigated by electrochemical measurements at 37℃ in a simulated body fluid (SBF). The electrochemical results show that the corrosion potential of Mn-contained alloys are increased compared to ternary Mg-3Zn-0.2Ca (wt.%) alloy, and 0.5wt.% Mn-contained alloy perfoms the best result.